Production and characterization of cationic cubosomes - Castro, Raphael Dias de (2019)
Cubosomes are nanostructures formed by the self-assembly of a lipid an aqueous solution, under certain experimental circumstances. Nanoparticles have been widely used as carriers of hydrophobic drugs, acting as a drug delivery method, with the potential to solve problems related to the drug, such as low solubility and instability. Theses facts are specially related to the cubic crystalline structure of these particles, in particular their large usable hydrophobic volume. The production of cubosomes relies on the self-assembly of lipids in excess of water, aided by the presence of a polymer acting as a emulsifier. The physicochemical properties of such particles can be characterized mainly by scattering techniques, namely small angle x-ray scattering (SAXS), dynamic light scattering (DLS), conventional and cryogenic transmission electron microscopy (TEM) and ζ (zeta) potential. This project aims the investigation of cubosomes production in the absence and presence of ionic liquids functionalized with alkyl chains, in order to produce cationic nanoparticles suitable for gene therapy, as in the case of DNA transfection. Cubosomes were prepared with two different lipid/polymer/water systems: phytantriol or monoolein stabilized with Puronic F127 in excess of water or buffer. Ionic liquid [C14mim][Cl] and cationic surfactant TTAB was added to these formulations and it was verified that the final dispersions contained cationic cubosomes. Particles positively charged with sizes between 300 nm and 350 nm and cubic crystalline internal structure were obtained and characterized.